A mixed method, multiperspective evaluation of a near peer teaching programme. Issue 1103 (24th February 2017) - Lydon, Sinéad; O'Connor, Paul; Mongan, Orla; Gorecka, Miroslawa; McVicker, Lyle; Stankard, Aiden; Byrne, Dara
Abstract : Purpose of study: Peer teaching (PT) has become increasingly popular. PT may offer benefits for students, tutors and institutions. Although resistance to PT has been identified among faculty, research has typically focused on students' experiences and perceptions, rather than those of the peer tutors or senior doctors/medical faculty. The current study comprised of a comprehensive, multiperspective evaluation of a near PT programme delivered by interns to final-year medical students in the Republic of Ireland. Study design: This study employed a mixed methods design, using both interviews and questionnaires to assess students' (n=130), interns' (n=49) and medical faculty's or senior doctors' (n=29) perceptions of the programme. Results: All three groups were emphatic about the programme's benefits, although senior doctors and faculty reported significantly more positive attitudes than the others. Mean ratings of the programme's value, out of 10, were 8.2 among students, 8.2 among interns and 9.1 among senior doctors and faculty. Challenges identified were largely organisational in nature. Perceived benefits for students included the informality of teaching sessions, increased opportunities in the clinical environment and improvements in exam preparedness. Perceived benefits for the interns included improvements in knowledge and teaching ability and experience as a role model. Conclusions: PT programmes have been posited as an 'easy fix' to growing numbers of students. However, it is apparent that PT has substantial value outside of this. Future research that conducts economic evaluations of such programmes and that collects objective data on teaching quality and student learning would be of much interest.